ผลของการควบคุมเนื้อหาบทเรียนด้วยผู้เรียน ในบทเรียนคอมพิวเตอร์ช่วยสอน ที่มีต่อความเข้าใจของนักเรียนชั้นประถมศึกษาปีที่ 6 ที่มีระดับผลสัมฤทธิ์ทางการเรียนในวิชาคณิตศาสตร์ต่างกัน - อรอุฬาร ไชยสุวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The objective of the research was to study the effect of learner control in computer-assisted instruction lesson on comprehension of prathomsuksa six students with different achievement levels in mathematics subject. The sample was 60 prathomsuksa six students, Phayathai School, academic year 2001 by simple random sampling method. Those students were designated into two groups, high and low achievement level in mathematics. Each group consisted of 30 students, and the students in each group were also divided into two groups, 15 each. The total was 4 groups. The simple random sampling method was employed to assign the computer-assisted instruction lesson with learner control to each group as follow; 1) The high achievement level students studied the Full Minus program. 2) The high achievement level students studied the Lean Plus program. 3) The low achievement level students studied the Full Minus program. 4) The low achievement level students studied the Lean Plus program. The data collected were analyzed by two-way analysis of variance at .01 significant level. The results were concluded as the following; 1) Students who study different versions of learner control, computer-assisted instruction lesson had different comprehension in mathematics at .01 significant level. 2) Students who had different achievement levels and study the same lesson had indifferent comprehension in mathematics at .01 significant level. 3) Students who had different achievement levels and study different lesson had indifferent comprehension in mathematics at .01 significant level.